Comunicação, novas tecnologias e informacionalização da política : o governo eletrônico no Mercosul - Martinuzzo, José Antonio (2006)
This Thesis is a result of a study about the electronic government s genesis in Brazil, Argentina, Uruguay and Paraguay, South-American countries, sharing trajectories amalgamated by a common factor: they had been formed as nations on the edge of the hegemonic power and so has been kept along the centuries. The recent history places them as protagonists of the Mercosul, a geopolitical and economic mobilization to face the globalization effects. In this articulated environment, but with dynamic movement among the countries, the national politics of electronic government are analyzed, as well as its format on the federal government s websites, searching to deﬁneacriticalpanelconcerning the new political-administrative practices based on digital sources. Starting from what could be considered the updating of the historical relation between communication, capital and politics, we verify two hypotheses: ﬁrstly,in spite of the emancipation and social mobilization potential of the Web, the e-gov would be seen as a strategy for adjusting governmental machines to the neoliberal framework of the informational capitalism. Secondly, establishing itself as a media, in the information society, inﬂuencedbythenewparadigmsof capitalism, the e-government would have the communication agents among its main characters. They would be responsible for formulating, planning and carrying out its process, according to the plane of adjusting the politics to the imperative media s modus operandi. In this process, the communicators get new political attributions.